Affording a Place: The Role of Persistent Structures in Social Navigation - Jenny Robins (Information Research: An International Electronic Journal)
Social navigation refers to the way people use the activities of others to direct their own behaviour. Using social navigation as a theoretical framework, it is possible to study and evaluate the patterned behaviour of occupants in cyberspace. It is proposed that an analysis of the type and extent of social navigation occurring in a collaborative virtual environment provides evidence that the environment houses a community. This paper reports findings from an ethnographic study of a distance education programme where three types of social navigation take place: guided behaviours, awareness behaviours and approbation behaviours. Also identified are the persistent structures in the environment that afford social navigation. A discussion of social navigation can inform researchers, designers and occupants of collaborative virtual environments.